A Phytonymic phraseology and linguocultural features of paremiological units - Aysu Mirzayeva (Jurnal Langua, 2021)
The article comparatively examines phytonomic phraseology, forming a branch of onomastic phraseology of English and Azerbaijani languages. Internal classification of onomastic phraseology is provided for this purpose and the criteria for designation of phytonymic phraseology are determined. Such a system of markers embraces lexical units that are more or less connected with the plant world, as well as words denoting the species of plants. Phytonymic phraseologies were selected from relevant lexicographic sources and grouped on the basis of materials of Azerbaijani and English languages. The research shows that phytonymic phraseology forms an independent group in the onomastic phraseology of each language. The characteristics of the development of phytonomic phraseology by species and type names were studied and high frequency of some species’ names in phytonomic phraseology was found out. The article also addresses the issues over adequacy and equivalence of phytonomic phraseology of diferent-system languages. The study in this area indicates considerable role of phytonomic phraseology in the verbalization of national-cultural indicators. Direct connection of ethnocultural marker and the code with the onym used in the composition was clarified in phytonomic phraseology.